Novel approach to hydroxy-group-containing porous organic polymers from bisphenol A - Wang, Tao; Zhao, Yan-Chao; Zhang, Li-Min; Cui, Yi; Zhang, Chang-Shan; Han, Bao-Hang (Beilstein Journal of Organic Chemistry, 2017)
We successfully employed bisphenol A and several different formyl-containing monomers as useful building blocks to construct a series of hydroxy-group-containing porous organic polymers in a sealed tube at high temperature. Fourier transform infrared and solid-state 13C CP/MAS NMR spectroscopy are utilized to characterize the possible structure of the obtained polymers. The highest Brunauer–Emmet–Teller specific surface area of the phenolic-resin porous organic polymers (PPOPs) is estimated to be 920 m2 g–1. The PPOPs exhibit a highest carbon dioxide uptake (up to 15.0 wt % (273 K) and 8.8 wt % (298 K) at 1.0 bar), and possess moderate hydrogen storage capacities ranging from 1.28 to 1.04 wt % (77 K) at 1.0 bar. Moreover, the highest uptake of methane for the PPOPs is measured as 4.3 wt % (273 K) at 1.0 bar.
Keywords: bisphenol A; carbon dioxide uptake; hydrogen storage; OH-containing; porous organic polymers

(untitled) - Yaghi, O. M.; Li, G.; Li, H. (Nature, 1995)

(untitled) - Yaghi, O. M.; Li, H. (J. Am. Chem. Soc., 1995)

(untitled) - Côté, A. P.; Benin, A. I.; Ockwig, N. W.; O'Keeffe, M.; Matzger, A. J.; Yaghi, O. M. (Science, 2005)

(untitled) - Wan, S.; Guo, J.; Kim, J.; Ihee, H.; Jiang, D. (Angew. Chem., Int. Ed., 2008)

(untitled) - Palkovits, R.; Antonietti, M.; Kuhn, P.; Thomas, A.; Schüth, F. (Angew. Chem., Int. Ed., 2009)

(untitled) - Liu, J.; Chen, Q.; Sun, Y.-N.; Xu, M.-Y.; Liu, W.; Han, B.-H. (RSC Adv., 2016)

(untitled) - Du, X.; Sun, Y.; Tan, B.; Teng, Q.; Yao, X.; Su, C.; Wang, W. (Chem. Commun., 2010)

(untitled) - Chan-Thaw, C. E.; Villa, A.; Katekomol, P.; Su, D.; Thomas, A.; Prati, L. (Nano Lett., 2010)

(untitled) - Kaur, P.; Hupp, J. T.; Nguyen, S. T. (ACS Catal., 2011)

(untitled) - Ghanem, B. S.; McKeown, N. B.; Budd, P. M.; Selbie, J. D.; Fritsch, D. (Adv. Mater., 2008)

(untitled) - Du, N.; Park, H. B.; Robertson, G. P.; Dal-Cin, M. M.; Visser, T.; Scoles, L.; Guiver, M. D. (Nat. Mater., 2011)

(untitled) - Wood, C. D.; Tan, B.; Trewin, A.; Niu, H.; Bradshaw, D.; Rosseinsky, M. J.; Khimyak, Y. Z.; Campbell, N. L.; Kirk, R.; Stöckel, E.; Cooper, A. I. (Chem. Mater., 2007)

(untitled) - Hu, X.-M.; Chen, Q.; Zhao, Y.-C.; Laursen, B. W.; Han, B.-H. (Microporous Mesoporous Mater., 2016)

(untitled) - McKeown, N. B.; Gahnem, B.; Msayib, K. J.; Budd, P. M.; Tattershall, C. E.; Mahmood, K.; Tan, S.; Book, D.; Langmi, H. W.; Walton, A. (Angew. Chem., Int. Ed., 2006)

(untitled) - Wu, D.; Xu, F.; Sun, B.; Fu, R.; He, H.; Matyjaszewski, K. (Chem. Rev., 2012)

(untitled) - Jiang, J.-X.; Su, F.; Trewin, A.; Wood, C. D.; Niu, H.; Jones, J. T. A.; Khimyak, Y. Z.; Cooper, A. I. (J. Am. Chem. Soc., 2008)

(untitled) - Weber, J.; Thomas, A. (J. Am. Chem. Soc., 2008)

(untitled) - Liu, X.; Xu, Y.; Jiang, D. (J. Am. Chem. Soc., 2012)

(untitled) - Kuhn, P.; Antonietti, M.; Thomas, A. (Angew. Chem., Int. Ed., 2008)

(untitled) - Zhao, Y.-C.; Cheng, Q.-Y.; Zhou, D.; Wang, T.; Han, B.-H. (J. Mater. Chem., 2012)

(untitled) - Zhao, Y.-C.; Wang, T.; Zhang, L.-M.; Cui, Y.; Han, B.-H. (ACS Appl. Mater. Interfaces, 2012)

(untitled) - Wang, T.; Zhao, Y.-C.; Luo, M.; Zhang, L.-M.; Cui, Y.; Zhang, C.-S.; Han, B.-H. (Polymer, 2015)

(untitled) - Katsoulidis, A. P.; Kanatzidis, M. G. (Chem. Mater., 2012)

(untitled) - Katsoulidis, A. P.; He, J.; Kanatzidis, M. G. (Chem. Mater., 2012)

(untitled) - Katsoulidis, A. P.; Kanatzidis, M. G. (Chem. Mater., 2011)

(untitled) - Wisser, F. M.; Eckhardt, K.; Wisser, D.; Böhlmann, W.; Grothe, J.; Brunner, E.; Kaskel, S. (Macromolecules, 2014)

(untitled) - Rose, M.; Klein, N.; Senkovska, I.; Schrage, C.; Wollmann, P.; Böhlmann, W.; Böhringer, B.; Fichtner, S.; Kaskel, S. (J. Mater. Chem., 2011)

(untitled) - Jang, B. N.; Wilkie, C. A. (Polym. Degrad. Stab., 2004)

(untitled) - Hunter, S. E.; Felczak, C. A.; Savage, P. E. (Green Chem., 2004)

(untitled) - Hunter, S. E.; Savage, P. E. (J. Org. Chem., 2004)

(untitled) - Dawson, R.; Laybourn, A.; Clowes, R.; Khimyak, Y. Z.; Adams, D. J.; Cooper, A. I. (Macromolecules, 2009)

(untitled) - Zhang, B.; Wang, Z. (Chem. Commun., 2009)

(untitled) - Makal, T. A.; Li, J.-R.; Lu, W.; Zhou, H.-C. (Chem. Soc. Rev., 2012)

(untitled) - Düren, T.; Sarkisov, L.; Yaghi, O. M.; Snurr, R. Q. (Langmuir, 2004)

(untitled) - Dawson, R.; Stevens, L. A.; Drage, T. C.; Snape, C. E.; Smith, M. W.; Adams, D. J.; Cooper, A. I. (J. Am. Chem. Soc., 2012)

(untitled) - Dawson, R.; Stöckel, E.; Holst, J. R.; Adams, D. J.; Cooper, A. I. (Energy Environ. Sci., 2011)

(untitled) - Wahby, A.; Ramos-Fernández, J. M.; Martínez-Escandell, M.; Sepúlveda-Escribano, A.; Silvestre-Albero, J.; Rodríguez-Reinoso, F. (ChemSusChem, 2010)

(untitled) - Yang, S.; Sun, J.; Ramirez-Cuesta, A. J.; Callear, S. K.; David, W. I. F.; Anderson, D. P.; Newby, R.; Blake, A. J.; Parker, J. E.; Tang, C. C.; Schröder, M. (Nat. Chem., 2012)

(untitled) - Sumida, K.; Rogow, D. L.; Mason, J. A.; McDonald, T. M.; Bloch, E. D.; Herm, Z. R.; Bae, T.-H.; Long, J. R. (Chem. Rev., 2012)

(untitled) - Dunne, J. A.; Mariwala, R.; Rao, M.; Sircar, S.; Gorte, R. J.; Myers, A. L. (Langmuir, 1996)

(untitled) - Furukawa, H.; Yaghi, O. M. (J. Am. Chem. Soc., 2009)

(untitled) - Llewellyn, P. L.; Maurin, G. (C. R. Chim., 2005)